2021
DOI: 10.1109/access.2021.3094766
|View full text |Cite
|
Sign up to set email alerts
|

A 24-Channel Neurostimulator IC With Channel-Specific Energy-Efficient Hybrid Preventive-Detective Dynamic-Precision Charge Balancing

Abstract: This paper presents the design, development, and experimental characterization of a 24channel programmable charge-balanced current-mode neurostimulator IC. Each channel is equipped with a quad-threshold voltage-based charge imbalance detection and a dedicated hybrid preventive-detective charge balancing circuit. The interplay of the preventive and detective control loops utilized for charge balancing has resulted in minimizing the power and timing overhead of the proposed strategy for maintaining a charge-neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…One of the biggest challenges in the field of sensory feedback via PNS concerns the design of the implantable system; in fact, this must have low energy consumption, have reliable and stable long-term operation, and, obviously, respect the biocompatibility characteristics, have small dimensions and must be able to communicate with the outside. The stimulation waveform used in this study was the symmetric biphasic square wave, as used in the literature both for PNS [12,[25][26][27][28][29] and for TENS [30][31][32][33][34][35] since it was shown to be able to elicit a more comfortable sensation among the other stimulation waveforms. The biphasic square wave settable parameters are the pulse amplitude (PA), the pulse width (PW), the pulse frequency (PF), and stimulation duration (i.e., the number of pulses).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest challenges in the field of sensory feedback via PNS concerns the design of the implantable system; in fact, this must have low energy consumption, have reliable and stable long-term operation, and, obviously, respect the biocompatibility characteristics, have small dimensions and must be able to communicate with the outside. The stimulation waveform used in this study was the symmetric biphasic square wave, as used in the literature both for PNS [12,[25][26][27][28][29] and for TENS [30][31][32][33][34][35] since it was shown to be able to elicit a more comfortable sensation among the other stimulation waveforms. The biphasic square wave settable parameters are the pulse amplitude (PA), the pulse width (PW), the pulse frequency (PF), and stimulation duration (i.e., the number of pulses).…”
Section: Methodsmentioning
confidence: 99%
“…The stimulation was a biphasic charge-balanced pulse, with an amplitude ranging from ±500 µA up to ±4 mA and a pulse width of 1 ms. The stimulation frequency used was 20 Hz for a stimulation duration of 10 s. The system with the lowest neutralization latency and power consumption, together with a programmable balancing precision and an innovative charge balancing technique, is the 24-channel neurostimulator IC described in [28]. Lastly, the strategy outlined in [29] includes the use of commercially accessible components in an implantable neurostimulation system for long-term behavioral and biological studies of neuropathic pain treatment.…”
mentioning
confidence: 99%
“…In addition to the electrode-specific DC offset, electrostatic charges generated on the skin due to many different reason (e.g., patient movement) could also significantly change the static DC level. Additionally, while the current pulses injected to the skin (for Z ESI measurement) are designed to be charge-balanced and biphasic, it has been shown that they could also result in charge accumulation on the electrode-skin interface in the long term, causing electrode and tissue damage [22], [23].…”
Section: F Input DC Level Correctionmentioning
confidence: 99%
“…Electrical stimulation techniques are categorized into 1) Voltage-mode, 2) Current-mode, and 3) Charge-mode stimulation. The most prevalent stimulation method used in implantable medical devices is constant-current stimulation, thanks to its inherent accurate charge transfer and compact implementation [1]- [3]. A notable difficulty in current-mode stimulation is the lack of control over the electrode-electrolyte output voltage since the residual potentials accumulate in long-term stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Cathodic pulse width modulation is done in [6] based on real-time interface impedance calculation. Furthermore, [1] employs anodic pulse modulation in addition to the offset current injection. However, the offset current injection requires the operation of an analog-to-digital converter (ADC) in an iterative way which contributes to high power consumption.…”
Section: Introductionmentioning
confidence: 99%